Podrivanje suvereniteta Bosne i Hercegovine / Undermining of the Sovereignty of Bosnia and Herzegovina - Milišić, Senija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The sovereign rights of Bosnia and Herzegovina are being disrupted, i.e. undermined through the attempts of contesting and dividing it. Global developments - from the Načertanije to Memorandum I or II have always facilitated the undermining of the Bosnia and Herzegovina‟s sovereignty. Vicinal irredentist 1 projects at the territorial expense of Bosnia and Herzegovina have essentially functioned in a form of alliance or agreement. This paper provides a brief overview of examples how the BH sovereignty has been undermined in certain historical periods. All periods are connected - they form a part of a process with the sole goal of contesting the sovereignty of Bosnia and Herzegovina; so the neighbors could disintegrate, carve up and divide the BH territory. The aggressive manipulation of the past for the purpose of achieving political goals receives the paper's special attention. Those goals involve making changes in the demographic and land ownership structure. In addition to external factors, the internal factors are also active. The main feature running through all periods has been the constant striving of eastern and western vicinal nationalisms to disintegrate Bosnia and Herzegovina.